Role of Sthanika Chikitsa by Ayurveda in Lichen Planus - Sheethal S; Geethakumari B; Swathi A C (AYUSHDHARA, 2025)
Lichen planus is a chronic inflammatory disease that affects the skin and the mucous membrane. Oral Lichen planus is classified under red and white lesions of oral cavity. Its oral manifestation can be the only sign or can involve other parts of the body. Here is a case report of a subject who was a part of a clinical trial comprising of 30 subjects equally divided into 2 groups. A case of Lichen planus in a thirty-one years old male patient who reported with discoloration, burning sensation on a part of dorsal, ventral surface of his tongue and bilateral buccal mucosa. Varied appearance from Wickham’s striae to pigmented, and erythematous lesion diagnosed as Oral Lichen planus is reported here. This can be closely related with Sarvasara Mukhapaka having similar characteristics. It disrupted his quality of life, and daily activities, even consumption of food, giving a negative effect on the subject’s overall health, emotional well-being and social life. This case showed major symptomatic relief and also changes in objective parameters like size and colorimetry in a short span of time the just by a local application of medicine. The case report aims to present the symptoms, study the effect of Haridradi Lepa, a Sthanika Chikitsa as a treatment modality for a case of Lichen Planus.